THE SCHOOL PRINCIPAL'S STRATEGY IN ENHANCING ACADEMIC ACHIEVEMENT OF STUDENTS THROUGH OLYMPIAD COACHING AT STATE JUNIOR HIGH SCHOOL 1 GALIS - Ratnawati, Rinta; Riza, Try Dieva Silvia; Wafi, Abdul (re-JIEM (Research Journal of Islamic Education Management), 2023)
Every educational institution aspires to foster students who have good intelligence, to realize this goal, the principal must implement a strategy that is considered appropriate. This research focuses on three main issues: first, the principal's approach to improving students' academic achievement through olympiads coaching; second, the implementation of strategies for improving students' academic achievement through olympiads coaching; and third, the supervision of the principal's strategy for fostering students' academic achievement through olympiads coaching. This research used a qualitative approach with a descriptive research design. Data collection was done by interview, observation, and documentation. The findings revealed that: first, the principal's strategies in fostering students' academic achievement through olympiads coaching include selecting professional teachers, optimizing olympiads coaching activities on a regular and scheduled basis, involving external teachers for science subjects, providing motivation, offering awards, installing banners, and fostering cooperation with parents; second, the implementation of these strategies runs smoothly and by the predetermined schedule; third, the supervision of the principal's strategies in improving students' academic achievement involves class visits to assess teacher performance and student learning progress.